2001
DOI: 10.4269/ajtmh.2001.64.247
|View full text |Cite
|
Sign up to set email alerts
|

A clinical and pharmacokinetic trial of six doses of artemether-lumefantrine for multidrug-resistant Plasmodium falciparum malaria in Thailand.

Abstract: Abstract. The efficacy-safety and pharmacokinetics of the six-dose regimen of artemether-lumefantrine (Coartem/ Riamet; Novartis Pharma AG, Basel, Switzerland) were assessed in a randomized trial in 219 patients (Ն 12 years old) with acute, uncomplicated Plasmodium falciparum malaria in Thailand. One hundred and sixty-four patients received artemether-lumefantrine and 55 received the standard treatment combination of mefloquine-artesunate. Both drugs induced rapid clearance of parasites and malaria symptoms. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
130
3
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(154 citation statements)
references
References 35 publications
20
130
3
1
Order By: Relevance
“…This is comparable with the previous study that showed a high treatment success rate (99.1 %) in the country (Jima et al, 2005b). The finding of this study is also in agreement with other studies in children and adults elsewhere using ACTs (Van Vugt et al, 1999, 2000Lefevre et al, 2001;Flade et al, 2005;Jima et al, 2005b;Piola et al, 2005;Piola et al, 2005;Guthmann et al, 2006;Van den Broek et al, 2006;Adama et al, 2007). In a study conducted in Senegal, the efficacy of AL was found to be 100 % when given as six doses, while it was found to be reduced by 3.6 % when given as four doses (Faye et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is comparable with the previous study that showed a high treatment success rate (99.1 %) in the country (Jima et al, 2005b). The finding of this study is also in agreement with other studies in children and adults elsewhere using ACTs (Van Vugt et al, 1999, 2000Lefevre et al, 2001;Flade et al, 2005;Jima et al, 2005b;Piola et al, 2005;Piola et al, 2005;Guthmann et al, 2006;Van den Broek et al, 2006;Adama et al, 2007). In a study conducted in Senegal, the efficacy of AL was found to be 100 % when given as six doses, while it was found to be reduced by 3.6 % when given as four doses (Faye et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…The present result also indicated the importance of maintaining the sixdose regimen for the treatment of uncomplicated falciparum malaria with regularly monitoring for its effectiveness especially in areas where multi-drug resistance falciparum malaria is common (Hastings et al, 2007). In this study, treatment with AL was also found to induce rapid clearance of malaria symptoms which is in agreement with previously conducted study in Ethiopia and clinical studies conducted elsewhere using ACTs (Bakshi et al, 2000;Lefevre et al, 2001;Jima et al, 2005b;Mulenga et al, 2006;Menard et al, 2008). In addition to its rapid parasitological and malaria symptoms clearance, AL showed high gametocyte reduction during the follow-up.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Coartemether (CoartemÒ, Novatis Pharma), a fixed dose combination of artemether and lumefantrine, combines the rapid but shortlived schizonticidal effect of artemether with the slower but more prolonged antimalarial effect of lumefantrine, a highly lipophilic aryl amino alcohol (Lefèvre et al 2001). When administered alone as a short treatment course over 2-3 days, lumefantrine gives a high cure rate but parasite and fever clearance time is slower than with artemether.…”
Section: Introductionmentioning
confidence: 99%